Pozzolanic Reactions of Metakaolin with Calcium Hydroxide: Review on Hydrate Phase Formations and Effect of Alkali Hydroxides, Carbonates and Sulfates - Kira Weise; Neven Ukrainczyk; Eduardus Koenders (Materials & Design, 2023)
Metakaolin (MK) has emerged as a highly promising supplementary material in low carbon binders for the construction industry. In wide range of applications, from lime to cement–based materials, its hardening performance relies on the pozzolanic reactivity between MK and calcium hydroxide (CH), resulting in the formation of diverse calcium-aluminate/silicate hydrates. The reaction sequence is affected by specific conditions dictated by the binder system employed in various applications. To advance the design of binders that reduce the carbon emissions, a systematical review on MK-based reactions is crucial. This review encompasses a broad range of MK/CH ratios and examines the effect of alkali hydroxides, carbonates and sulfates. The focus is on the formation and stability of pozzolanic hydrate phases over time and under different curing temperatures. Additionally, the review addresses the characteristics that directly affect MK reactivity, such as the (calcined) clay structure and the dissolution of the reactants. The systematic findings shed light on the hydrate phase assemblage, enabling a better understanding of the reaction mechanisms in complex systems, like MK cementitious blends. The results of this review serve as a valuable foundation for the development of novel “low-carbon” binder designs and compositions for both cementitious and lime-based binders.